Twelve-month outcomes in overweight/obese users with mental disorders following a multi-element treatment including diet, physical activity, and positive thinking: The real-world “An Apple a Day” controlled trial - Giusti, Laura; Bianchini, Valeria; Aggio, Annalisa; Mammarella, Silvia; Salza, Anna; Necozione, Stefano; Alunno, Alessia; Ferri, Claudio; Casacchia, Massimo; Roncone, Rita (Frontiers in Psychiatry, 2022)
Overweight and obesity and metabolic diseases are not often prevented, identified, or adequately treated among persons with mental illness. The present study aimed to evaluate the 12-month effectiveness of a real-world weight loss transdiagnostic intervention in overweight/obese participants affected by mental disorders under psychopharmacological treatment. We conducted a real-world, controlled, pragmatic outpatient trial. We recruited and consecutively allocated 58 overweight/obese adults under psychopharmacological treatment from a mental health outpatient unit and 48 overweight/obese adults from a hypertension and cardiovascular prevention outpatient unit, and assigned them to an intervention or treatment usual as condition (TAU) enriched by lifestyle advice. Participants in both intervention groups took part in a diet programme (the modified OMNIHeart dietary protocol) and monitoring of regular aerobic activity. A brief group programme (‘An Apple a Day’ Metacognitive Training, Apple-MCT) was added in the intervention group of participants affected by mental disorders. The primary outcome was weight loss. Secondary outcomes included anthropometric, clinical, and metabolic variables. Psychopathology and health-related quality of life were also evaluated in the psychiatric sample. At 12 months, both intervention groups showed a more marked mean decrease in weight (6.7 kg, SD: 3.57) than the TAU group (0.32 kg, SD: 1.96). Both intervention groups exhibited a statistically significant difference in the proportion of participants who lost 5% (59.3%) or 10% (25.4%) of their baseline weight compared to those included in the TAU groups who lost 5% (7.7%) or 10% (0%) of their baseline weight; 92.3% of TAU participants recorded less than 5% weight loss versus the intervention groups (15.3%). Compared to when the study began, in the intervention groups, at 12 months, the mean changes revealed a statistically significant decline in total cholesterol, triglycerides, low-density lipoprotein cholesterol, fasting glucose levels, and a positive HDLc concentration increase compared with the control groups. Furthermore, the participants affected by mental disorders included in the intervention group reported improved health-related quality of life. Our findings suggest the need to implement integrated interventions based on a modified OMNIHeart dietary protocol, physical activity, and modification of cognitive style in overweight/obese users with mental disorders.